(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the theoretical and methodological foundations of medical-ecological competence development, integrative methodology and effectiveness of its improvement are studied. Also, an integrative method of developing medical-ecological competence in medical university students was analyzed.